Pre-competitive state anxiety level between female and male combat sport athletes SUKMA 2018 / Nur Fazila Md Sidek - Md Sidek, Nur Fazila (2019)
This study was conducted to determine the level of anxiety level among combat sport before the Sukma Games 2018 competition. The study focuses on the state anxiety level between female and male among combat sport athletes before the Sukma tournament. There were 25 male combat sport athletes and 25 female combat sport athlete ages 16-18 years old and 19-21 years old were chosen from Sukma Games 2018 as subjects. The instrument used in this study was Competitive State Anxiety Inventory-2 (CSAI-2) questionnaire and demographic questionnaire. The subjects were given a questionnaire that was distributed one day before the game to be answered with a required time. This study found that combat sport from both genders showed the same result of anxiety level. The Independent T-test was used to identify the difference of state anxiety level between gender which the results showed that there was no significant difference on state of anxiety level between male and female which (p = 0.498 ) and one way-ANOVA was used to identify the difference between type of combat sport which (p = 262). In a nutshell, it can be concluding that gender has no effect on state anxiety levels in combat sports. Further studies should include larger scale group to determine the effect of gender on state anxiety levels better.